Civil-military relations and global security governance : strategy, hybrid orders and the case of Pakistan - Baciu, Cornelia-Adriana (Abingdon, Oxon ; New York, NY : Routledge, 2021)
This book investigates the relationship between international security governance, democratic civil-military relations and the relevance of strategy, as well as of absolute and relative gains, in norms formation in hybrid orders. Highlighting caveats of the legacy of Huntington's paradigm of military professionalism, the book applies a robust methodology and data collected in four sample regions in Pakistan. It gauges the effects of international and local actors' support in the Security Sector Reform domain and examines instances of civil-military interactions and military transition. The book also analyses determinants and strategies that can influence them to demonstrate the impact of global governance in norms diffusion, as well as of absolute and relative utility gains and incentives in normative change. The author generates a new theory pertaining to international organisations and actors as determinants of transformation processes and consequently sheds new light on the issue of global security governance, especially its impact on civil-military relations and democratisation in hybrid orders. The book will be of interest to scholars and practitioners in the field of global governance, civil-military relations, grand strategy and foreign policy as well as Asian politics, South Asian studies, peace, security and strategic studies, International Relations and political science in more general.
1. Introduction 2. Global Security Governance, Multi-Track Diplomacy and Democratic Change 3. Civil-Military Relations and Military Change 4. Mechanisms of Democratic Control in Hybrid Orders 5. Methodology and Research Design 6. Military Change, Democratisation and Non-Linear Transformation 7. The Impact of Non-State Actors on Security Sector Reforms and Democratic Oversight 8. Key Determinants of Civil-Military Relations 9. Conclusion. Towards a Theory of Civil-Military Relations and International Security Governance.
OCLC-licensed vendor bibliographic record.
Keywords: Civil-military relations -- Pakistan; Civilians in war -- Pakistan; Public safety -- Pakistan; POLITICAL SCIENCE / Government / Comparative; POLITICAL SCIENCE / International Relations / General; POLITICAL SCIENCE / Peace